The Importance Of Harmonizing Science And Religion For The Life Of Generation Z: Pentingnya Harmonisasi Sains Dan Agama Bagi Kehidupan Generasi Z - Bayani, Dzatil (Yayasan Insan Cendekia Nusantara, 2024)
Background: This research focuses on the integration of science and religion as two domains of knowledge that are often seen as contradictory but actually complementary. The formulation of the problem raised is how these two disciplines can collaborate to answer contemporary global challenges, such as environmental crises, technological developments, and character building of the younger generation. The method: used is a systematic literature study with an interdisciplinary perspective, including philosophical, theological, and scientific analysis. Main Findings. First, efforts to integrate science and religion offer a solid ethical foundation in scientific research, especially in the realm of bioethics and technological ethics. Second, Generation Z, which grew up in the digital era, needs a synergy between technological mastery and spiritual values to form a civilized and responsible character. Contributively, this research adds a practical dimension to the literature that previously focused more on philosophical or theological aspects alone. In conclusion, the integration of science and religion not only bridges the epistemological gap, but also provides a holistic framework for sustainable solutions to global problems. Recommendations include the implementation of interdisciplinary curricula, cross-field dialog, and research ethics training so that religious values and scientific findings can interact productively in modern society